Library lion - Knudsen, Michelle; Hawkes, Kevin (Cambridge, Mass. : Candlewick Press, 2006)
A lion starts visiting the local library but runs into trouble as he tries to both obey the rules and help his librarian friend.
Parents' Choice, January 2006
Wilson's Children, October 2010
School Library Journal starred, August 2006
Book Links (A.L.A.), March 2010
Booklist, August 2006
New York Times, January 2007
Keywords: Lion -- Juvenile fiction; Libraries -- Juvenile fiction; Obedience -- Juvenile fiction; Lion -- Fiction; Libraries -- Fiction; Obedience -- Fiction; Lions -- Fiction; Libraries -- Fiction; Obedience -- Fiction